Revitalisasi Distributed Control System (DCS) untuk Meningkatkan Keandalan Operasional di SHAFTHI dengan Pendekatan Kode Etik Profesi Insinyur - Kelvin Manik; Ardyono Priyadi; Fidelis Galla Limbong (Jurnal Elektronika dan Otomasi Industri, 2026)
The revitalization of control systems is an essential part of ensuring the reliability, safety, and operational efficiency of industrial facilities. One of the strategic projects undertaken is the revitalization of the Distributed Control System (DCS) at SHAFTHI, which aims to update hardware and software to meet current operational requirements. In its implementation, the adoption of the Engineer's Professional Code of Ethics serves as the primary foundation to ensure that every stage of work is carried out professionally, with integrity, and prioritizing safety, health, security, and the environment (HSE). This engineering practice emphasizes the application of ethical principles such as competence, responsibility to the public, objectivity, and compliance with technical regulations. By prioritizing the code of ethics, the revitalization of the DCS not only results in a more reliable and modern system but also provides assurance that the technical decisions made are aligned with ethical values and the interests of stakeholders. This implementation is expected to serve as an example of the application of engineering professionalism in addressing the challenges of technological modernization while maintaining public trust in the engineering profession.